TRUE METABOLIZABLE ENERGY AND DIGESTIBILITY OF FIVE Vigna unguiculata VARIETIES IN CHICKENS - Luis Armando Sarmiento-Franco; E. Gorocica; L. Ramirez; J. Castillo; R. Santos; M. Diaz (Tropical and Subtropical Agroecosystems, 2010)
This study was carried out to evaluate the effect of heat-treatment on grain true metabolizable energy (TME), dry matter and gross energy digestibilities of five Vigna unguiculata varieties: H82, T782, TM97, C666 y XL. The grain of the former three varieties were heat-treated, and offered raw or cooked, whereas grain of the late two varieties were used only row, resulting in a total of eight treatments. The heat treatment consisted of watering the grains with boiling water for 30 minutes and drying at 60°C. Forty-five Hubbard male chickens (2.1 ± 0.2 kg) housed in individual wire pens were used to evaluate the treatments. Five chickens from each treatment were fed 40 g of treated grain in mash form, using the force-feeding technique. Additionally, five fasted chickens were used to calculate the endogenous energy and DM losses. The data were submitted to an analysis of variance according to the randomized statistical model; to evaluate the effect of heat treatment orthogonal contrasts were performed. There were no significant differences in all the variables neither among varieties nor between heat treatments (P>0.05). TME values in this study were similar to those found in the literature and equivalent to the TME value of soybean meal, a conventional feedstuff used in the poultry industry.